Self‐Assembly of a Trithioorthoformate‐Capped Cyclophane and Its Endohedral Inclusion of a Methine Group. Issue 58 (24th September 2019) - Collins, Mary S.; Shear, Trevor A.; Smith, Elizabeth K.; Strain, S. Michael; Zakharov, Lev N.; Johnson, Darren W.
Abstract: An unusual trithioorthoformate‐capped cyclophane cage was assembled via antimony‐activated iodine oxidation of thiols as confirmed by 1 H‐NMR spectroscopy and X‐ray crystallography. The disulfide bridges can undergo desulfurization with hexamethylphosphorous triamide (HMPT) at ambient temperature to capture a trithioether cyclophane cage capped by the trithioorthoformate. In both cages a methine proton points directly into the small cavity. This unexpected structure is hypothesized to have formed as a result of haloform insertion during oxidation. Abstract : Using antimony‐activated iodine oxidation, an unusual trithioorthoformate‐capped disulfide cyclophane cage was synthesized. Sulfur extrusion was shown to be successful, providing the trithioether analogue. Additionally, yield optimization allowed for >58 % yield.